Nitric oxide regulation of migrating motor complex: randomized trial of NG‐monomethyl‐l‐arginine effects in relation to muscarinic and serotonergic receptor blockade. (30th July 2015) - Halim, M. A.; Gillberg, L.; Boghus, S.; Sundbom, M.; Karlbom, U.; Webb, D.‐L.; Hellström, P. M.
Abstract: Aim: The migrating motor complex (MMC) propels contents through the gastrointestinal tract during fasting. Nitric oxide (NO) is an inhibitory neurotransmitter in the gastrointestinal tract. Little is known about how NO regulates the MMC. In this study, the aim was to examine nitrergic inhibition of the MMC in man using N G ‐monomethyl‐l ‐arginine (l ‐NMMA) in combination with muscarinic receptor antagonist atropine and 5‐HT3 receptor antagonist ondansetron. Methods: Twenty‐six healthy volunteers underwent antroduodenojejunal manometry for 8 h with saline or NO synthase (NOS) inhibitorl ‐NMMA randomly injected I.V. at 4 h with or without atropine or ondansetron. Plasma ghrelin, motilin and somatostatin were measured by ELISA. Intestinal muscle strip contractions were investigated for NO‐dependent mechanisms usingl ‐NMMA and tetrodotoxin. NOS expression was localized by immunohistochemistry. Results: l ‐NMMA elicited premature duodenojejunal phase III in all subjects but one, irrespective of atropine or ondansetron.l ‐NMMA shortened MMC cycle length, suppressed phase I and shifted motility towards phase II. Pre‐treatment with atropine extended phase II, while ondansetron had no effect.l ‐NMMA did not change circulating ghrelin, motilin or somatostatin. Intestinal contractions were stimulated byl ‐NMMA, insensitive to tetrodotoxin. NOS immunoreactivity was detected in the myenteric plexus but not in smooth muscle cells. Conclusion: Nitric oxide suppresses phase III of MMC independent of muscarinic and 5‐HT3 receptors as shown by nitrergic blockade, and acts through a neurocrine disinhibition step resulting in stimulated phase III of MMC independent of cholinergic or 5‐HT3 ‐ergic mechanisms. Furthermore, phase II of MMC is governed by inhibitory nitrergic and excitatory cholinergic, but not 5‐HT3 ‐ergic mechanisms.